2006
DOI: 10.1063/1.2396893
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic method for levitation of small living animals

Abstract: Ultrasonic levitation of some small living animals such as ant, ladybug, and young fish has been achieved with a single-axis acoustic levitator. The vitality of ant and ladybug is not evidently influenced during the acoustic levitation, whereas that of the young fish is reduced because of the inadequacy of water supply. Numerical analysis shows that the sound pressures on the ladybug’s surface almost reach the incident pressure amplitude p0 due to sound scattering. It is estimated that 99.98% of the acoustic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 17 publications
2
90
1
5
Order By: Relevance
“…This setup creates a standing wave that levitates particles in the nodes and can suspend liquid droplets of up to half-wavelength diameter (4mm at 40kHz in air) [48]. Similar setups have levitated living insects [57], small fishes in a ball of water [47] and even small food items (e.g., [11,27]). However, a complete food delivery system, including mid-air transportation and delivery to the end user, has not been attempted to date.…”
Section: Acoustic Levitationmentioning
confidence: 99%
“…This setup creates a standing wave that levitates particles in the nodes and can suspend liquid droplets of up to half-wavelength diameter (4mm at 40kHz in air) [48]. Similar setups have levitated living insects [57], small fishes in a ball of water [47] and even small food items (e.g., [11,27]). However, a complete food delivery system, including mid-air transportation and delivery to the end user, has not been attempted to date.…”
Section: Acoustic Levitationmentioning
confidence: 99%
“…tungsten, was successfully levitated for the first time using standing wave ultrasonic levitation. Recently Xie and Wei reported the successful levitation of small living animals such as an ant, ladybird and small fish with a standing wave acoustic levitator [21] and their experiments showed that the vitality of the small animals was not impaired during levitation.…”
Section: Fundamentals Of Ultrasonic Levitation 21 Standing Wave Levimentioning
confidence: 99%
“…[1][2][3] Although initially used to measure the speed of sound in gasses, recent work has focused on exploiting this phenomena for the non-contact trapping, positioning, and manipulation of objects. 4 For example, Foresti et al used an array of transducers to levitate and manipulate millimetre sized objects in air, 2 Thalhammer et al forced living organisms into the focal plane of an optical tweezer system, 5 and Petersson et al integrated acoustic traps with a microfluidic channel to demonstrate the separation of lipids from red blood cells.…”
mentioning
confidence: 99%
“…Knowledge of the stiffness of the optical trap and measurement of the micro-sphere's displacement from its equilibrium position enables the force exerted on the micro-sphere to be calculated. A single silica micro-sphere (Bang Laboratories Ltd, 5.20 lm mean diameter, variance 10%-15%, and density 2.0 g/cm 3 ) was trapped at the focus of the laser. The particle's motion was measured at 150 frames/s using image tracking.…”
mentioning
confidence: 99%